Mapping the congruence between larval morphology and molecular phylogeny: Convergent adaptations of freshwater shrimps (Decapoda, Caridea) - Pantaleão, João A. F.; Peres, Pedro A.; Mantelatto, Fernando L. (Zoologica scripta, 2025)
Colonization of freshwater by marine organisms and the evolutionary history of exchanges between salt and freshwater habitats is not only related to osmoregulatory capabilities, but also to optimize reproductive and developmental strategies, as abbreviated rather than extended planktonic development. Composed of more than 270 species, Macrobrachium is the most specious shrimp genus in the Palaemonidae family. It is considered a promising model for reconstructing evolutionary transitions between the two types of life cycle found in caridean shrimps, that is, extended larval development (ELD) and abbreviated larval development (ALD). The objective of this study was to integrate the morphology of the first post‐embryonic stage and molecular data under a phylogenetic framework to elucidate the evolution of life history types (ALD and ELD) and test the hypothesis of convergent evolution at the morphology of the first post‐embryonic stage represented by similar traits in non‐related species. Our results revealed that the classical ALD/ELD categorization combines multiple characters instead of representing a closed set of traits, and certain characters have phylogenetic signal (evolutionary constraints), while others probably reflect evolutionary convergences related to adaptation to freshwater environment.